PENGUATAN PERAN LEMBAGA EKONOMI SYARIAH MELALUI KEBIJAKAN BERKELANJUTAN - Muhammad Irfan; Naufal Luthfi Alifa; Daffa Achmad Fakih; Dimas Abdul Hadi (Al-Iqtishad: Jurnal Ekonomi Syariah, 2025)
Islamic economic institutions are expected to serve as key drivers of equitable and inclusive development grounded in the values of maq?????id al-shar????ah. However, current realities indicate limited integration of sustainability principles and a dominant short-term profit orientation, which constrains the social contribution of Islamic institutions to public welfare. This study focuses on public policies aimed at strengthening the capacity and role of Islamic economic institutions in promoting a sustainable financial system; the implementation of sustainable governance (good governance) to enhance stability and public trust in Islamic financial institutions; the institutional integration of green finance and social finance; and cross-sector collaboration strategies among government, academia, and industry to reinforce an inclusive and globally adaptive Islamic economic ecosystem. The research employs a descriptive qualitative method using a literature review and policy analysis approach. The findings indicate that: (1) strengthening Islamic economic institutions requires comprehensive public policy synergies encompassing regulatory, fiscal, and social dimensions; (2) sustainable governance enhances the legitimacy and competitiveness of Islamic financial institutions; (3) the integration of green finance and social finance plays a strategic role in achieving a socially just and environmentally sustainable economic system; and (4) cross-sector collaboration is a critical factor in formulating adaptive policies aligned with maq?????id al-shar????ah amid global change.